2016
DOI: 10.3402/gha.v9.31280
|View full text |Cite
|
Sign up to set email alerts
|

Alarming attrition rates among HIV-infected individuals in pre-antiretroviral therapy care in Myanmar, 2011–2014

Abstract: BackgroundHigh retention rates have been documented among patients receiving antiretroviral therapy (ART) in Myanmar. However, there is no information on human immunodeficiency virus (HIV)-infected individuals in care before initiation of ART (pre-ART care). We assessed attrition (loss-to-follow-up [LTFU] and death) rates among HIV-infected individuals in pre-ART care and their associated factors over a 4-year period.DesignIn this retrospective cohort study, we extracted routinely collected data of HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…First, despite the higher rates of retention in care, most of the attrition happened during the first year after ART initiation. This finding is consistent with the studies reported previously in Myanmar and in other settings (7, 911). Attrition was also found to be significantly associated with the expected risk factors, a CD4 count ≤ 50 cells/mm 3 and having baseline weight ≤ 50 kg.…”
Section: Discussionsupporting
confidence: 94%
“…First, despite the higher rates of retention in care, most of the attrition happened during the first year after ART initiation. This finding is consistent with the studies reported previously in Myanmar and in other settings (7, 911). Attrition was also found to be significantly associated with the expected risk factors, a CD4 count ≤ 50 cells/mm 3 and having baseline weight ≤ 50 kg.…”
Section: Discussionsupporting
confidence: 94%
“…It was related to a policy of assessment for eligibility for ART initiation during the study period. Though we do not know the status of those not on ART, a previous study in Myanmar has detected alarmingly high attrition during pre-ART care [15]. There is evidence that PLHIV often encountered barriers in accessing ART-related services (both before and after ART uptake) even in contexts where these services are freely available [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies using adult HIV seropositive patient data (aged ≥ 15 years of age) from IHC programme have shown that the attrition rates in pre-ART care and ART care is 32% and 16%, respectively (5-year cohort analysis with 13.7 months median duration of follow-up) [5,11]. Compared to these results, private sector adult ART cohort in Myanmar had a relatively higher attrition rate of 20% during 5-years follow-up [12].…”
Section: Introductionmentioning
confidence: 99%